Design of Detection and Counting System of Human Detector Camera Based on Opencv Using Python at Makassar Aviation Polytechnic - Faiqah, Faiqah; Wening, Ida Umboro Wahyu Nur; Rahman P, Abdul (PT FORMOSA CENDEKIA GLOBAL, 2025)
Real-time monitoring of learning activities is crucial to ensure that all cadet and lecturer activities take place according to the rules. Deviations or delays in learning can be corrected immediately so that teaching and learning activities remain according to plans and targets. The purpose of the research is to design a user interface using the OpenCV-based Python programming language in learning activities. This research uses the Research and Development method by ADDIE model. Testing instruments use black box and functional. Design of the monitoring system utilizes Internet of Things (IoT) technology through a website to facilitate remote monitoring. The feasibility test by paying attention to the features of the monitoring system in this application runs effectively and can be implemented.